Dental care delivery in the context of the COVID-19 pandemic: a bibliometric analysis and review of emerging trends - Łaganowski, Kacper; Majewski, Jakub; Nijakowski, Kacper (Journal of Stomatology, 2025)
The COVID-19 pandemic significantly disrupted dental care delivery, prompting a shift towards urgent treatments and the widespread adoption of tele-dentistry. The current study presented a comprehensive bibliometric analysis of 88 publications retrieved from the Web of Science database, investigating global trends in dental services during the COVID-19 pandemic. Citation and key word co-occurrence analyses were performed using VOSviewer, highlighting dominant thematic clusters and collaboration networks. Three major trends emerged: a decline in routine dental procedures with increased emergency services, heightened psychological stress among dental professionals and patients, and emergency care protocols and treatment adjustments to maintain patient care. Results indicated a significant shift towards urgent dental services to mitigate aerosol exposure, with conservative procedures declining and surgical treatments increasing. Notably, the pandemic catalyzed the adoption of tele-dentistry and reinforced the importance of enhanced infection control measures, including high-level of personal protective equipment, improved ventilation systems, and antiseptic mouth rinses. Psychological effects on both dental professionals and patients emerged as a key theme, with elevated anxiety levels influencing service utilization and staff well-being. Geographically, the United States and England contributed the highest number of publications, reflecting robust research activity in these regions. This analysis provided valuable insights into how the dental profession adapted to the unprecedented challenges of the COVID-19 pandemic, and underscored the importance of robust protocols for future public health crises.